THE EFFECT OF TILT ANGLE AND MOUNTING HEIGHT ON BIFACIAL GAIN AND ANNUAL ENERGY YIELD OF A ROOFTOP BIFACIAL PV SYSTEM: A PVSYST PARAMETRIC ANALYSIS IN THE HUMID TROPICAL CLIMATE OF SOUTH SULAWESI - Heriani; Muhammad Iqbal Nikmatullah (PT. Radja Intercontinental Publishing, 2026)
Bifacial photovoltaic (PV) modules capture solar irradiance on both front and rear surfaces, with the rear-side contribution quantified as bifacial gain (BG), highly sensitive to tilt angle and mounting height above the roof surface. A systematic simulation study simultaneously varying both parameters for the humid tropical climate of South Sulawesi, Indonesia has not been found in publicly indexed databases (Google Scholar, Scopus, SINTA, Garuda, Neliti; last searched 10 June 2025). This study presents a parametric simulation dataset through 20 PVsyst 7.3.1 variants combining five tilt angles (5–25°) with four mounting heights (0.30–1.00 m) for a 10.8 kWp grid-connected bifacial rooftop system (5.2334°S, 119.5047°E; GHI = 1,855 kWh/m²/yr). Results show tilt 10° consistently maximizes annual energy yield (E_grid) across all heights, consistent with low-latitude theory and field measurements by Khoo et al. (2014), peaking at 17,631 kWh/yr (PR = 0.871; BG = 8.0%) at H = 1.00 m. Albedo sensitivity analysis shows BG ranging 6.1–10.2% across albedo 0.15–0.30, with a disproportionate +2.2 pp increase at the 0.25→0.30 step, consistent with the nonlinear albedo–BG relationship reported by Deline et al. (2020), though the underlying mechanism requires field confirmation. This study is a simulation-based parametric analysis without on-site field validation, a limitation stated explicitly throughout; results should not be treated as experimentally validated values.